Pelatihan Strategi Pemasaran Pisang “Sang Mulyo” - Festy Putri Ramadhani; Mumpuni Ningsih, Gumoyo; Bakhtiar, Ary; Muhammad Shodiq, Wahid (Universitas Muhammadiyah Malang, 2025)
Purpose –The purpose of this community service activity was to enhance the local community's knowledge and skills in digital marketing, specifically focusing on the marketing of the local banana variety “Sang Mulyo.” By providing training in marketing strategies and the use of digital platforms, this initiative aimed to empower the residents of Sri Mulyo Village to expand their market reach, optimize their product sales, and increase the competitiveness of local micro-enterprises. Additionally, the program sought to support the long-term economic sustainability of the village through the integration of digital marketing solutions. Design/methodology/approach – This research utilized a community engagement-based approach, combining training, mentoring, and simulation methods. The development of online training media was implemented to enhance the digital marketing skills of SMEs in Srimulyo Village, Dampit District, specifically for